Diversidade de Agaricales (Basidiomycota) na Reserva Biológica Walter Egler, Amazonas, Brasil Diversity of Agaricales (Basidiomycota) in the Reserva Biológica Walter Egler, Amazonas, Brazil - Helenires Queiroz de Souza (Acta Amazonica, 2004)
Foi realizado um estudo dos representantes da Ordem Agaricales Clements (Hymenomycetes, Basidiomycotina), ocorrentes na Reserva Biológica Walter Egler, situada na Estrada AM-010, Manaus-Itacoatiara, Km 64, Latitude 02° 43' S e Longitude 59° 47' W, Rio Preto da Eva, Amazonas. A área abrange 709 ha de floresta de terra firme primária. As coletas foram realizadas no período de dezembro de 2000 a junho de 2001 e seguiu-se a metodologia usual para identificação de Agaricales. Foram estudadas um total de 39 espécies, distribuídas em 13 gêneros e seis famílias: Polyporaceae: Pleurotus sp.; Hygrophoraceae: Hygrocybe cf. megistospora, Hygrocybe aff. miniceps, Hygrocybe occidentalis var. scarletina, e mais oito espécies de Hygrocybe indeterminadas; Tricholomataceae: Clitocybe sp., Hydropus sp.1 e Hydropus sp.2, Macrocystidia sp., Marasmiellus sp., Marasmius bellus, Marasmius haedinus var. haedinus,Marasmius cf. leoninus, Marasmius cf. mazatecus, Marasmius cf. ruber,Marasmius cf. setulosifolius, Marasmius tageticolor, Marasmius cf. variabiliceps var. variabiliceps, Marasmius sp.1, Marasmius sp.2, Marasmius sp.3 e Marasmius sp.4, Tricholoma sp.; Agaricaceae: Agaricus sp.1 e Agaricus sp.2, Lepiota sp., Cystoderma sp.; Entolomataceae: Entoloma cf. azureoviride, Entoloma cf. cystidiophorum, Entoloma strigosissima, Entoloma sp.; Russulaceae: Lactarius panuoides. Destas, Entoloma azureoviride, Hygrocybe miniceps, Lactarius panuoides, Marasmius cf. mazatecus, Marasmius cf. setulosifolius e Marasmius variabiliceps var. variabiliceps, provavelmente, estão sendo aqui citadas pela primeira vez, para o Brasil. Com exceção de Marasmius tageticolor, as demais espécies são citadas pela primeira vez, para a Reserva Egler. São fornecidas tabelas com a ocorrência das espécies de acordo com o gradiente topográfico (baixio, vertente, platô) e seus respectivos habitats. A study of the order Agaricales Clements (Hymenomycetes, Basidiomycotina), occurring in the Reserva Biológica Walter Egler was carried out from December 2000 to June 2001. The area of study is situated at Road AM-010, Manaus-Itacoatiara, km 64, Latitude 02° 43' S and Longitude 59° 47' W, Rio Preto da Eva, in the State of Amazonas, with a total area of 709 ha of terra firme rain forest. The fungi collected were identified based on traditional methodology for identification of Agaricales. A total of 39 species were studied, distributed in 13 genera and six families: Polyporaceae: Pleurotus sp.; Hygrophoraceae: Hygrocybe cf. megistospora, Hygrocybe aff. miniceps, Hygrocybe occidentalis var. scarletina and eight indeterminate species of Hygrocybe; Tricholomataceae: Clitocybe sp., Hydropus sp.1 and Hydropus sp.2, Macrocystidia sp., Marasmiellus sp., Marasmius bellus, Marasmius haedinus var. haedinus, Marasmius cf. leoninus, Marasmius cf. mazatecus, Marasmius cf. ruber, Marasmius cf. setulosifolius, Marasmius tageticolor, Marasmius cf. variabiliceps var. variabiliceps, Marasmius sp.1, Marasmius sp.2, Marasmius sp.3 and Marasmius sp.4, Tricholoma sp.; Agaricaceae: Agaricus sp.1 and Agaricus sp.2, Lepiota sp., Cystoderma sp.; Entolomataceae: Entoloma cf. azureoviride, Entoloma cf. cystidiophorum, Entoloma strigosissima, Entoloma sp.; Russulaceae: Lactarius panuoides. Entoloma azureoviride, Hygrocybe miniceps, Lactarius panuoides, Marasmius cf. mazatecus, Marasmius cf. setulosifolius and Marasmius variabiliceps var. variabiliceps, apparently are here cited for the first time from Brazil. With exception of Marasmius tageticolor, all species are cited here for the first time as occurring in Egler Forest. The tables with the species occurrence, in accordance with the topographical gradient (sand bank, incline, plateau) and its respective habitat, are supplied.